Multi-level outcomes for young adults with acquired brain injury through a remote intensive cognitive rehabilitation approach: a pilot intervention study. (28th January 2022) - Gilbert, Christianna; Mooradian, Grace; Citorik, Anne; Gilmore, Natalie; Kiran, Swathi
ABSTRACT: Objective: To investigate the effects of the Intensive Cognitive and Communication Rehabilitation (ICCR) program for young adults with acquired brain injury (ABI) using a quasi-experimental pilot intervention study design while transitioning to remote implementation. Method: Twelve young adults with chronic ABI (treatment n = 7; control n = 5) participated in ICCR (i.e., lectures, seminars, individual cognitive rehabilitation (CR), technology training) for six hours/day, four days/week, for one or two 12-week semesters. Outcomes included classroom metrics, individual therapy performance, including Goal Attainment Scaling (GAS), standardized cognitive-linguistic assessments, and participation and health-related quality of life (QOL) measures. Results: In the first semester (in-person and remote), treatment participants significantly improved in classroom exams; individual therapy (i.e., memory, writing, GAS); executive function and participation measures, but not QOL. In the second semester (remote), treatment participants significantly improved in classroom exams; essay writing; individual therapy (i.e., writing and GAS); and memory assessment, but not in participation or QOL. Treatment participants enrolled in consecutive semesters significantly improved in classroom exams, individual therapy (i.e., memory), participation and QOL, but not on standardized cognitive assessments. Controls demonstrated no significant group-level gains. Conclusion: These preliminary results highlight the benefit of intensive, integrated, and contextualized CR for this population and show promise for its remote delivery.